2014
DOI: 10.2460/ajvr.75.5.453
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of subcutaneous versus intramuscular administration of ceftiofur crystalline-free acid to bearded dragons (Pogona vitticeps)

Abstract: A single dose of CCFA (30 mg/kg) administered IM or SC to bearded dragons yielded plasma concentrations of ceftiofur and its metabolites > 1 μg/mL for > 288 hours. The SC route would be preferred because of less variability in plasma concentrations and greater ease of administration than the IM route. Future studies should include efficacy data as well as evaluation of the administration of multiple doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Indeed, prolonged plasma concentrations in American alligators following intramuscular injection at the same 30-mg/kg dose administered to bearded dragons was observed, but plasma concentrations were greater than those reported for bearded dragons. 7 Compared to bearded dragons, American alligators achieved an average maximum plasma concentration 1.6-fold higher (14.1 vs 23.2 lg/ml) and an average AUC 2.2-fold greater (1.89 vs 4.24 h • mg/ml). 7 The time to reach maximum plasma concentrations in American alligators (72 h) was markedly longer compared to bearded dragons (18.7 h), green iguanas (6.10 h), and ball pythons (2.17 h).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, prolonged plasma concentrations in American alligators following intramuscular injection at the same 30-mg/kg dose administered to bearded dragons was observed, but plasma concentrations were greater than those reported for bearded dragons. 7 Compared to bearded dragons, American alligators achieved an average maximum plasma concentration 1.6-fold higher (14.1 vs 23.2 lg/ml) and an average AUC 2.2-fold greater (1.89 vs 4.24 h • mg/ml). 7 The time to reach maximum plasma concentrations in American alligators (72 h) was markedly longer compared to bearded dragons (18.7 h), green iguanas (6.10 h), and ball pythons (2.17 h).…”
Section: Discussionmentioning
confidence: 90%
“…7 Compared to bearded dragons, American alligators achieved an average maximum plasma concentration 1.6-fold higher (14.1 vs 23.2 lg/ml) and an average AUC 2.2-fold greater (1.89 vs 4.24 h • mg/ml). 7 The time to reach maximum plasma concentrations in American alligators (72 h) was markedly longer compared to bearded dragons (18.7 h), green iguanas (6.10 h), and ball pythons (2.17 h). 1,7,31 The reported average t 1/2 values for CCFA following IM administration in other reptiles were 64.3-75.3 h but t 1/2 appears to be approximately twofold longer in alligators (143 h).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…dose of CCFA maintaining therapeutic concentrations of ceftiofur for 5–8 days (Witte et al ., ). Ceftiofur crystalline‐free acid pharmacokinetics have also been studied in goats (Dore et al ., ), horses (Collard et al ., ; Giguere et al ., ; Hall et al ., ; Credille et al ., ; Fultz et al ., ), and zoological species including Asian elephants ( Elephas maximus ) (Adkesson et al ., ), California sea lions ( Zalophus californianus ) (Meegan et al ., ), alpacas (Dechant et al ., ), ball pythons ( Python regius ) (Adkesson et al ., ), bearded dragons ( Pogona vitticeps ) (Churgin et al ., ), guinea fowl ( Numida meleagris ) (Wojick et al ., ), and American black ducks ( Anas rubripes ) (Hope et al ., ). Pharmacokinetic and toxic effects of ceftiofur sodium have been studied previously in grass carp ( Ctenopharyngodon idella ) (Somjetlertcharoen, ), but no studies involving the extended release formulation of ceftiofur CCFA have been reported previously in fish to the authors’ knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies for terbinafine hydrochloride have previously been documented in birds, horses, dogs, cats, rabbits, and rats (Bechert, Christensen, Poppenga, Le et al, 2010;Bechert, Christensen, Poppenga, Fahmy, & Redig, 2010;Emery, Cox, & Souza, 2012;Evans, Emery, Cox, & Souza, 2013;Hosseini-Yeganeh and McLachlan, 2001;Sakai et al, 2011;Sun et al, 2007;Wang et al, 2012;Williams, Davis, & KuKanich, 2010). However, antifungal pharmacokinetics studies in squamates are limited (Brosnan, Pypendop, Barter, & Hawkins, 2006;Churgin, Musgrave, Cox, & Sladky, 2014;Gamble, Alvarado, & Bennett, 1997;Tuttle et al, 2006;Van Waeyenberghe et al, 2010), and those involving terbinafine are nonexistent.…”
mentioning
confidence: 99%